The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/10915818221094487
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of L-β-Aminoisobutyric Acid (L-BAIBA): Subchronic Toxicity Study in Sprague Dawley Rats

Abstract: L-3-Aminoisobutyric acid (L-BAIBA) is an endogenous compound in human metabolism when thymine and valine undergo catabolism. L-BAIBA represents one of the two isomers of BAIBA in biological systems. BAIBA has been shown to reduce body fat percentage via an increase in fatty acid oxidation and a decrease in hepatic lipogenesis. However, no toxicological effects of L-BAIBA in animals or humans have been established. The present study was designed to evaluate the safety and toxic potentials of this compound, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Meanwhile, the concentration of L-BAIBA in circulation is negatively related to cardio-metabolic risk factors (Kitase et In addition, it is worthwhile noting that L-BAIBA has excellent pharmacological properties, such as stable property and convenient to store. These evidences suggest that L-BAIBA may be an excellent potential therapeutic agent, and due to its potential medicinal value, there have been toxicological and pharmacokinetic studies on L-BAIBA (Krieger et al 2022 ;Shanmugasundaram et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the concentration of L-BAIBA in circulation is negatively related to cardio-metabolic risk factors (Kitase et In addition, it is worthwhile noting that L-BAIBA has excellent pharmacological properties, such as stable property and convenient to store. These evidences suggest that L-BAIBA may be an excellent potential therapeutic agent, and due to its potential medicinal value, there have been toxicological and pharmacokinetic studies on L-BAIBA (Krieger et al 2022 ;Shanmugasundaram et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worthwhile noting that L-BAIBA has favorable pharmacological properties, such as stability and convenient storage. L-BAIBA, being a promising therapeutic agent, has been the subject of toxicological and pharmacokinetic studies (Krieger et al 2022 ; Shanmugasundaram et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical applications, it is important to achieve drug efficacy without toxic side effects. A toxicological study showed that L-BAIBA can be delivered without adverse effects at 900 mg/kg/day for 90 days, which is the highest level tested ( 83 ). In addition, in human studies, approximately 2–20% Caucasians and 50% Asians were found to be deficient in AGXT2 ( 84 , 85 ), with high urinary D-BAIBA levels.…”
Section: Prospects Of Baiba Being Used As An Exercise Pill?mentioning
confidence: 99%